Maqasid Syari’ah sebagai Landasan Reformasi Hukum Perceraian dan Hak Asuh Anak dalam Konteks Modern - Ilham Rahmani; Rahman Alwi (Journal of Family and Sharia, 2025)
Islamic family law reform, particularly in the areas of divorce and child custody, has become a crucial issue in line with the increasing divorce rate and demands for gender justice and child protection in the modern era. Family law practice is often still dominated by a textual-formal approach that is not fully responsive to social and humanitarian dynamics. This study aims to analyze the role of maqasid al-syari’ah as a philosophical and methodological foundation in the reform of divorce and child custody law. This study uses a qualitative approach with a normative-philosophical legal research method through a literature review of primary, secondary, and tertiary legal sources, which are analyzed using deductive and inductive content analysis techniques. The results show that maqāṣid al-syarī‘ah, particularly the principles of hifz al-din, hifz al-nafs, hifz al-nasl, and hifz al-‘aql, play a significant role in driving a paradigm shift in Islamic family law from textual legalism to substantive justice. The maqasid approach has proven capable of accommodating the protection of women’s and children’s rights and bridging the gap between sharia norms and modern social realities. The implications of this research confirm that maqāṣid al-syarī‘ah can serve as a normative and methodological basis for reforming regulations and practices of religious justice that are more humane, gender-just, and child-oriented in the context of contemporary Islamic family law.